Albanian peasant economy in the aftermath of property right reforms: A review of the 20th century tenure history - Edvin Zhllima; Klodjan Rama (Martor, 2014)
This study reviews some of the most important changes in Albanian land tenure. This historical description of the tenure systems from the Ottoman period to the recent reform will provide a deeper understanding of the evolution of tenure arrangements in Albania. It will point out their policy objectives, their implementation in practice and their impact on structural features of the agriculture system in Albania.
Keywords: 330; land tenure; land reform; peasantry; Albania; Southeast Europe